Prevalence of abnormal cervical cytology and HPV DNA positivity among HIV positive women - Malik, Sunita; Kumari, Supriti; Gaikwad, Harsha S.; Mishra, Archana; Bharadwaj, Mausumi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The relationship among HIV, HPV, and development of CIN is complex and incompletely understood. Present study is undertaken to find out the prevalence and relationship of abnormal cervical cytology and HPV infection in HIV positive women. Methods: This was a cross-sectional, case control study conducted on 95 HIV seropositive and 95 seronegative women. Specimen was collected from the cervix for HPV DNA testing, subtyping and cytology. Results: HPV DNA positivity was higher in seropositive group (18.6% vs. 7.4%). Premalignant conditions were found only in seropositive group. At CD4 count <249 HPV DNA positivity was 53%, at 250-499 the percentage of HPV DNA positivity was 31% and at >500 HPV DNA positivity was 19%. Conclusions: Prevalence of abnormal cytology and HPV DNA positivity is higher amongst HIV positive women and there is an association between HPV DNA positivity with lower CD4 counts.